(untitled) (Journal of Social Sciences Review, 2023)
This article aims to explore the lived experiences of six women leaders and their leadership practices for improving institutional performance at the university level. The article explains how authenticity in leadership attributes influences team effectiveness and institutional performance. The qualitative approach was adopted for this article. The population of the article was all university women leaders of Khyber Pakhtunkhwa. The Sample was chosen from HoDs at the University of Swat. Data were collected from 06 university women leaders through in-depth interviews. A purposive sampling technique was adopted to approach the participants. Obtained results prove that university women leaders significantly improve institutional performance through their authentic leadership practices. Moreover, findings suggest that authenticity plays an imperative role in the improvement of team effectiveness.